NILAI SOSIAL BUDAYA UPACARA RITUAL SIRAMAN AIR TERJUN SEDUDO DI KABUPATEN NGANJUK - Ana Leyliana; Bagus Wahyu Setiawan (Institut Islam Nahdlatul Ulama Temanggung, 2022)
Abstract This study aims to examine the socio-cultural value of the ritual ceremony of the Sedudo waterfall shower in Ngliman Village, Sawahan District, Nganjuk Regency. This research was completed using a qualitative descriptive method. The data collection technique used is observation, and documentation, the results of qualitative research are written in the form of a written report. The results of the study show that Nganjuk Regency is one of the regencies that is still developing tourism based on cultural tourism. The form of this culture is, the ritual procession of the Sedudo waterfall splash ceremony which is held every Suro month (Javanese calendar). The smooth running of these activities is supported by people who have high social values, the following are the manifestations of the social values ​​of the Ngliman Village community; (a) compassion, which comes from the element of feeling from within the community to always be responsible for creating peace, (b) mutual cooperation, the Ngliman community always works together to enliven the ritual ceremony of the Sedudo waterfall splash from beginning to end. Gotong royong is very necessary to realize community groups in traditional ritual ceremonies of the Sedudo waterfall splash, (c) harmony, this social value of harmony is created in the Ngliman community who respect and support each other in cultural activities at the ritual ceremony of the Sedudo waterfall splash, (d) ) cooperation, the social value of cooperation has always been attached to the ngliman community. The principle of the value of cooperation, namely; 1) oriented towards achieving a goal in the form of smooth running of the ritual ceremony of the Sedudo waterfall shower, 2) paying attention and prioritizing common interests, 3) mutual benefit and 4) the value of tolerance.